PENERAPAN METODE PROTOYPE PADA PERANCANGAN E-BUSINESS AIR MINUM ISI ULANG BAROKAH : Prototype Method, E-Business, Refill Drinking Water - Kurniawan, Tomi; Rahmawati, Noni; Ramadani, Rio; -, Suroto; Syah , Thamrin (LP2M Universitas Nurdin Hamzah, 2025)
The rapid advancement of technology has influenced business processes, including refill drinking water businesses. This study applies the Prototype Method in designing an e-business system for